Thoracic aorta calcification but not inflammation is associated with increased cardiovascular disease risk: results of the CAMONA study - Blomberg, Björn A.; de Jong, Pim A.; Thomassen, Anders; Lam, Marnix G. E.; Vach, Werner; Olsen, Michael H.; Mali, Willem P. T. M.; Narula, Jagat; Alavi, Abass; Høilund-Carlsen, Poul F. (European journal of nuclear medicine and molecular imaging, 2017)
Purpose Arterial inflammation and vascular calcification are regarded as early prognostic markers of cardiovascular disease (CVD). In this study we investigated the relationship between CVD risk and arterial inflammation ( 18 F-FDG PET/CT imaging), vascular calcification metabolism (Na 18 F PET/CT imaging), and vascular calcium burden (CT imaging) of the thoracic aorta in a population at low CVD risk. Methods Study participants underwent blood pressure measurements, blood analyses, and 18 F-FDG and Na 18 F PET/CT imaging. In addition, the 10-year risk for development of CVD, based on the Framingham risk score (FRS), was estimated. CVD risk was compared across quartiles of thoracic aorta 18 F-FDG uptake, Na 18 F uptake, and calcium burden on CT. Results A total of 139 subjects (52 % men, mean age 49 years, age range 21 – 75 years, median FRS 6 %) were evaluated. CVD risk was, on average, 3.7 times higher among subjects with thoracic aorta Na 18 F uptake in the highest quartile compared with those in the lowest quartile of the distribution (15.5 % vs. 4.2 %; P < 0.001). CVD risk was on average, 3.7 times higher among subjects with a thoracic aorta calcium burden on CT in the highest quartile compared with those in the lowest two quartiles of the distribution (18.0 % vs. 4.9 %; P < 0.001). CVD risk was similar in subjects in all quartiles of thoracic aorta 18 F-FDG uptake. Conclusion Our findings indicate that an unfavourable CVD risk profile is associated with marked increases in vascular calcification metabolism and vascular calcium burden of the thoracic aorta, but not with arterial inflammation.